18 CPAU vs MAU: Acute Chest Pain Unit Provides Rapid Specialist Assessment, Early Coronary Intervention and Reduced Length of Stay for Patients Admitted with Suspected Acute Coronary Syndrome at a Large District General Hospital. (6th June 2015) - Balaji, Gothandaraman; Baheerathan, Aravinthan
Abstract : Aims: Acute chest pain is a common presenting complaint to the Accident and Emergency department (A&E) in the United Kingdom and is responsible for 20–30% of A&E attendances. Often these patients require admission to Medical Admissions Unit (MAU) for further assessment and treatment. In order to improve the quality of care provided to patients admitted with suspected Acute Coronary Syndrome (ACS), we have introduced the Chest pain Acute Unit (CPAU) within our Cardiology unit, whereby these patients are admitted directly from A&E to CPAU and not to MAU. The aim of our study was to assess 3 important parameters (1. specialist review, 2. coronary procedure/intervention, 3. length of stay) as markers of effectiveness of the CPAU compared to our routine care, where patients were admitted from A&E to the MAU and then to the Cardiology ward. Methods: 621 consecutive suspected ACS patients who were admitted from A&E directly to CPAU over a period of 15 months (July 2011 – Oct 2012) were followed-up to assess the effect of the CPAU on time to specialist assessment, time to cardiac catheter lab and time to discharge. This data was compared to the data obtained for patients who were treated with routine care prior to the initiation of the CPAU. A paired t-test was performed to assess for statistical significance. Results: With routine care, the mean time to Specialist Cardiologist assessment was 21 h 2 min, this significantly improved to a mean time of 6 h 17 min following the CPAU initiation (p < 0.0001). Additionally, the mean duration from door to cardiac catheter lab time post-CPAU improved to 39.6 h, in contrast to 63.33 h previously (p < 0.0001). The mean length of inpatient stay was markedly reduced to 2.59 days compared to 4.66 days pre-CPAU (p < 0.0001). Conclusion: The implementation of a CPAU is an effective tool for providing a better clinical service in the management of ACS, particularly by providing timely specialist review, quicker diagnostic and therapeutic intervention and by significantly reducing the duration of inpatient stay.